Risk Analysis For Sustainable Broccoli Cultivation : A Case Study From Ngablak District Magelang Regency - Widadie, Fanny (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
Broccoli farming has a high production risk due to climate change, pest attacks, and fluctuations in production input prices. The purpose of this study is to analyze the income and risks of broccoli farming, factors affecting broccoli production, and farmers' risk preferences. This research is useful in understanding the risks of farmers in broccoli farming. The location of the investigation was deliberately determined (purposive method), namely, in Sumberejo Village, Ngablak District, Magelang Regency, Central Java Province, which is a vegetable center area. The sampling was carried out randomly on 60 broccoli farmers. The analytical tools used to measure risk are the values of the coefficients of variation and resistance. Factors that affect production using the Cobb-Douglas production model, and those that affect risk using Ordinary Least Square (OLS) with the De Janvry model approach. The results showed that the coefficients of variation in production and income were 0.76 and 0.88, and the risk aversion coefficient was quite high with an average of 1.125. Factors that affect production are land, seeds, pesticides, chemical fertilizers, and organic fertilizers. Education, institutions, land area, and income influence farmers' behavior toward risk.